INSECURE SEBAGAI KRISIS PEMAHAMAN HAKIKAT MANUSIA: MENCARI JATI DIRI DIANTARA JASAD DAN RUH MELALUI MURAQABAH - Liberto, Quellativa Clevaranu Salsabilah; Assifa Retno Devanti (Program Studi Ilmu Tasawuf Universitas Pangeran Diponegoro Nganjuk, Jawa Timur, 2025)
The phenomenon of insecurity is one of the crises experienced by many individuals in the modern era and is often understood solely from a psychological perspective. However, this crisis also reflects an imbalance between the physical (jasad) and spiritual (ruh) aspects within the human being. The purpose of this study is to examine insecurity as an existential crisis that arises from the disconnection between humans and their true nature as beings composed of both body and soul. Using a literature review method, this research explores various perspectives from psychology, philosophy, and Islamic spirituality. The findings indicate that insecurity is not merely a matter of low self-esteem or past trauma, but also a reflection of the loss of awareness of the soul’s role in human life. The effort to realign the body and soul through contemplative practices such as muraqabah is offered as a solution to restore inner balance. This paper suggests that a holistic understanding of the human being is essential in addressing the issue of insecurity in today’s world.